1992
DOI: 10.1088/0953-8984/4/25/017
|View full text |Cite
|
Sign up to set email alerts
|

The photoelectron bandstructure of molybdenum disulphide

Abstract: An experimental electronic bandstructure of molybdenum disulphide has been determined from angle-resolved ultraviolet photoelectron spectroscopy (ARUPS) measurements: polar-angle-dependent ARUPS at a photon energy of 21.2 eV allows the authors to obtain an approximate plot of dispersion parallel to the basal face while photon-energy-dependent ARUPS at normal emission gives a plot of dispersion perpendicular to this face. The experimental bandstructure is compared with three calculations and, while there is a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
7
10
0
Order By: Relevance
“…This is corroborated by numerous PES studies (see, e.g., Ref. [34] for 2H-MoS 2 ). LEED studies [35] showed that the geometric structure of bulk 2H-MoS 2 is retained and has the same lattice parameters on the surface, the only difference being a compression of the interlayer distance by an amount of up to 5%.…”
Section: Theoretical Modelsupporting
confidence: 80%
“…This is corroborated by numerous PES studies (see, e.g., Ref. [34] for 2H-MoS 2 ). LEED studies [35] showed that the geometric structure of bulk 2H-MoS 2 is retained and has the same lattice parameters on the surface, the only difference being a compression of the interlayer distance by an amount of up to 5%.…”
Section: Theoretical Modelsupporting
confidence: 80%
“…The absence of interlayer interaction leads to strong modifications of the electronic and optical properties in all the monolayer systems. They are found to be direct-band-gap semiconductors with the VBM and CBM at the K point of the Brillouin zone, in contrast to the indirect band gaps of the bulk materials with the VBM at the point and the CBM at about 0.55 -K. 15,[25][26][27][28][29][30] An indirect-directband-gap crossover with decreasing sample thickness has been exemplified for MoS 2 experimentally. 12 While the CBM of a WS 2 monolayer has not been studied, a shift of the VBM from the to the K point due to the absence of interlayer interaction has been demonstrated by angle-resolved photoelectron spectroscopy.…”
Section: Resultsmentioning
confidence: 89%
“…The overall feature of the present band structure is quite consistent with previous ARPES studies. [11][12][13] From one panel to another [see Fig. 2(a) versus Fig.…”
Section: Experimental and Theoretical Detailsmentioning
confidence: 99%
“…9 Despite these remarkable findings, the causes and origin of this unpredictable behavior have not been so far understood. Even though the bulk electronic structure has been extensively examined over the last 40 years by theoretical and experimental studies, [10][11][12][13][14][15] the effect of van der Waals (vdW) interactions on the indirect-to-direct gap transition as a function of the MoS 2 thickness has not been directly observed. [16][17][18] We demonstrate that a novel MoS 2 (0002) surface state exists at the point, characterized by a larger (indirect) band gap than the bulk.…”
Section: Introductionmentioning
confidence: 99%